The Brazilian fact-checkers criteria: an analysis of the guiding purposes, principles, and routines of this journalistic practice - Rodríguez-Pérez, Carlos; Seibt, Taís (Brazilian journalism research, 2022)
ABSTRACT – This research aims to know the purposes, motivations, and routines of the fact-checking practice in Brazil. We developed a self-administered questionnaire to understand the perceptions of journalists. The sample (n=29) expressed their level of agreement with a group of statements. The results show the central purpose is to detect and combat false and misleading content on digital channels. Also, the principle of transparency regarding news sources and data that support a content evaluation is firmly appreciated. Differences emerge related to the ease of using digital tools between IFCN members and non-members. Age is a relevant factor regarding the pressures during the journalism practice. RESUMO – Buscamos conhecer propósitos, motivações e rotinas da prática de fact-checking no Brasil, a partir das percepções dos jornalistas. A pesquisa se baseia em questionário autogestionado, no qual 29 respondentes manifestaram seu grau de concordância com um conjunto de afirmações. Como resultados, temos que o principal propósito consiste em detectar e combater conteúdos falsos e enganosos nos canais digitais e que a transparência em mostrar fontes e dados que sustentam a classificação do conteúdo é um valor fortemente compartilhado. Há variações quanto à facilidade em usar ferramentas digitais entre membros e não-membros da IFCN, assim como diferenças nas pressões ao exercício profissional conforme a faixa etária. RESUMEN – Este artículo busca conocer los propósitos, motivaciones y rutinas de la práctica del fact-checking en Brasil a partir de las percepciones de los periodistas. La investigación se base en un cuestionario autogestionado, en el cual 29 periodistas manifestaron su nivel de acuerdo sobre un conjunto de afirmaciones. Los resultados muestran que el principal propósito consiste en detectar y combatir contenidos falsos y engañosos en los canales digitales y que la transparencia en mostrar fuentes y datos que sustenten la calificación del contenido es un principio fuertemente compartido. Hay diferencias en cuanto a la facilidad de uso de las herramientas digitales entre aquellos miembros y no miembros de la IFCN, así como en la influencia de presiones en el ejercicio profesional por grupos etarios.